2007
DOI: 10.1111/j.1462-5822.2007.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone-like DNA binding protein of Streptococcus intermedius induces the expression of pro-inflammatory cytokines in human monocytes via activation of ERK1/2 and JNK pathways

Abstract: Summary Streptococcus intermedius

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 59 publications
3
35
0
Order By: Relevance
“…Our data demonstrate that endogenous HlpA is preferentially expressed at the bacterial surface in the stationary growth phase, which is in line with the study of Katsube et al, who reported that the histone-like protein MDP1 of Mycobacterium smegmatis accumulates in cell wall fractions in the stationary phase (18). Furthermore, our findings correlate with previous studies reporting the release of HlpA during the stationary growth phase (22,35). In the exponential phase, HlpA is required intracellularly to execute its physiological role in nucleoid formation (1), but even though endogenous HlpA is maintained intracellularly, recombinant HlpA-His was not able to bind to the bacterial surface.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our data demonstrate that endogenous HlpA is preferentially expressed at the bacterial surface in the stationary growth phase, which is in line with the study of Katsube et al, who reported that the histone-like protein MDP1 of Mycobacterium smegmatis accumulates in cell wall fractions in the stationary phase (18). Furthermore, our findings correlate with previous studies reporting the release of HlpA during the stationary growth phase (22,35). In the exponential phase, HlpA is required intracellularly to execute its physiological role in nucleoid formation (1), but even though endogenous HlpA is maintained intracellularly, recombinant HlpA-His was not able to bind to the bacterial surface.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the heparin-binding histone-like protein A (HlpA) from S. bovis was recently shown to be present in cell wall extracts and was a target of the humoral immune response in patients with colon cancer (38). Several other studies confirmed that this conserved bacterial protein from Streptococcus pyogenes, which is 95.6% identical to S. gallolyticus HlpA, had affinity for lipoteichoic acid (LTA), an intrinsic component of the gram-positive cell wall (22,35,43). Furthermore, proteomic analysis of the bacterial surface of S. pyogenes revealed that HlpA is a surface-linked protein (33).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The stimulatory effect of rS.i.-HLP was cooperative by costimulation with LTA. 29 Upregulation of serum pro-inflammatory cytokines, complements, and soluble interleukin 2 receptor in PBC was reported. 30 Therefore, kinetic studies including cytokine and complement changes in our mice model are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Along with other streptococci, S. mutans encodes a single NAP, known as HLP (SMU.589), which is an essential protein in streptococci (48). Previous studies have shown that HLPs of streptococci resemble E. coli HU protein in terms of nucleoid structuring (24,47,51) and may play a potential role in infection-induced inflammation during streptococcal pathogenesis (66,67,77). In this study, we found that HLP also plays an important role in silencing the expression of foreign genes acquired by S. mutans.…”
Section: Discussionmentioning
confidence: 99%